Survey of Mycotoxins Present in Florida Pastures Across Time, Locations, and Grass Species - Hui-Ling Liao; Kaile Zhang; Vijay Verma; Haihua Wang; Brittany Justesen; Joseph Walter; Valerie Mendez; Ann Blount; Cheryl Mackowiak; Marcelo Wallau; Robbie Jones; Ko-Hsuan Chen; et al. (EDIS, 2025)
The toxicity of grasses caused by mycotoxins has led to economic losses in the United States due to the health impact on livestock feeding on it. Florida's warm and humid weather is favorable for the growth of mycotoxin-producing fungi on grasses. The JECFA has provided evaluations and risk management for some high-risk mycotoxins; however, more research is needed in Florida to determine the maximum levels of these mycotoxins, how different environmental conditions affect these levels, and the specialized risk management to prevent animals from getting sick. Our Extension agents were able to collect and examine 195 grass samples from 13 ranchers across dry and wet seasons in Florida. In this publication, we summarized the results for our ranchers to learn more about (1) what (dominant) mycotoxins are generally present in Florida’s pastures, (2) what grass species could harbor more of these mycotoxins, and (3) what seasons or locations may favor these dominant mycotoxins.